Pertumbuhan ikan koi (Cyprinus rubrofuscus) menggunakan sistem budidaya recirculating aquaculture sistem (RAS) dan akuaponik - Masyruroh, Siti; Firmani, Ummul (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
Koi fish, a popular freshwater ornamental fish with high economic value, is known for its attractive shape and color. Intensive cultivation of koi (Cyprinus rubrofuscus) using sistems such as Recirculatory Aquaculture Sistem (RAS) and aquaponics presents profitable business opportunities. However, land conversion for development reduces cultivation areas and water quality, necessitating innovations to ensure the sustainability of fish farming. The RAS sistem utilizes filters to recycle water, while aquaponics uses plant media for filtration. Research conducted from February 7 to March 19, 2024, at UD. Pojok Koi Farm, Gresik, East Java, aimed to compare koi growth under these two cultivation sistems. The results indicate that neither the aquaponics sistem nor RAS significantly affected koi length and survival, but both had an impact on weight gain and feed conversion ratio (FCR). Water quality, including pH, temperature, and DO, plays a crucial role in koi growth. pH and temperature remained within suitable ranges, while DO levels met the minimal requirements for koi in both sistems. Good water quality and effective filtration sistems support the growth and health of koi fish.